Design and performance research on eliminating multiple reflections of solar radiation within compound parabolic concentrator (CPC) in hybrid CPV/T system. (May 2016) - Xie, Huling; Wei, Jinjia; Wang, Zexin; Yang, Gao; Ma, Qiuming
Highlights: A new-type eliminating multiple reflections CPC (EMR) was designed. Best concentration plane were defined to conduct optical performance study. Material consumption assessment method was developed. Comparative research among EMR, full CPC (FUL) and half truncation CPC (HAL). The tradeoff between cost and optical performance of EMR is the best. Abstract: Aimed at developing a concentrating flat-plate photovoltaic-thermal (CPV/T) system of low cost and high output, a new-type eliminating multiple reflections CPC (EMR) with a geometric concentration ratio 4× was designed, and the best concentration plane of EMR, full CPC (FUL) and half truncation CPC (HAL) were defined to conduct optical performance study. Afterward, the material consumption assessment method was developed to evaluate the reflector and support material consumption of EMR, FUL and HAL, and the Monte-Carlo simulation was developed to calculate the values of uniformity and optical efficiency of those three types of CPCs. Additionally, the formula method was employed to figure out the optical efficiency of EMR in simple and convenient way, and the EMR related experiments were carried out to testify the theoretical results of EMR figured out via the Monte-Carlo simulation and formula method in different total solar irradiance (TSI) and ratio of direct normal irradiance (DNI) to TSI. Finally, the research shows that the experimental results of EMR are in good agreement with the theoretical data of EMR calculated via the Monte-Carlo simulation and formula method, and that the uniformity on best concentration plane is better than that of outlet aperture, indicating that not only the reflector and support material consumption of EMR is the minimum among those of EMR, FUL and HAL, but also the uniformity and optical efficiency of EMR is the best among them according to the comparative research with the material consumption assessment method and Monte-Carlo simulation adopted. Especially, the material consumption of EMR is about one-half less than that of FUL when geometric concentration ratio is 4×, meanwhile, the uniformity of EMR on best concentration plane is about 20% more than that of FUL and the optical efficiency of EMR is about 2% more than that of FUL. Furthermore, theoretical and test results show that the optical efficiency of EMR can exceed 80% when the ratio of DNI to TSI is equal to or greater than 0.8, and then a new CPV/T system was assembled with EMR, PV/T and low-precision solar tracking subsystem, and the overall efficiency of the CPV/T system can exceed 71%. In conclusion, it is obvious that the EMR has more extensive application potential compared to FUL and those traditional truncation CPCs such as HAL.